The Green Dilemma: When Environmental Good Depletes Financial Good in Emerging Economies - Chipimo, Mubanga Lackson; Bwalya, John; Kanyanga, Joseph Katongo (SEISENSE (PRIVATE) LIMITED, 2025)
Purpose- This paper aims to examine the relationship between environmental sustainability practices and firm profitability within Zambia’s agro-food sector, assessing both short-term financial effects and strategic implications.Design/Methodology- The study adopted explanatory sequential mixed-methods. Using fixed and random effects regression models, panel data from listed agro-food firms (2014-2024) were analysed. It was followed by thematic analysis of sustainability reports and a semi-structured interview with firm-level sustainability officers.Findings- The quantitative results showed a significant negative relationship between environmental performance and short-term profitability. The Random Effects model revealed a coefficient of –15.739 (p = 0.0006) for the Environmental Score, indicating that higher sustainability scores are associated with lower immediate ROA. Governance was a strong positive predictor of profitability (β = 23.08, p < 0.01). Qualitative findings highlighted long-term benefits. Revenue was statistically insignificant.Practical Implications- Firms need to pursue environmental strategies that are scalable and context sensitive. Regulatory supports, enhancement of technical capacity, and alignment of stakeholders are also critical to make firms’ investment in sustainability compatible with their profitability targets.Originality- As one of the first African emerging-market studies to focus only on environmental sustainability–profitability trade-offs, the paper makes an original contribution, methodologically by the application of an ISO-aligned environmental scoring framework in a context-specific and theoretically by extending Stakeholder and Signaling Theory to illustrate how environmental practices may act as a credible signal for long-term value